Hybrid teaching approach at Romanian Language and Literature in PISA 2018, Romania - Octavia Borș (Revista de Știinţe Educaţiei, 2022)
In recent years, teaching became an important subject of public debate, as a critical area of educational reform in Romania. There is little consensus about what is expected of Romanian teachers, some standpoints inclining towards taking a more constructivist approach in teaching. However, there is little scientific evidence about the teaching practices of Romanian teachers, for public debate to rely on. PISA 2018 (Romania) gives access to data about the frequency of 5 teaching practices, as perceived by students at Romanian Language and Literature lessons. The analysis of these practices suggests that, in their students` perception, Romanian teachers have a hybrid approach of teaching, with a predominance of directed instruction. Also, according to the students, other frequent practices in Romanian language and literature class are teacher support and teachers` stimulation of reading engagement. For the future, more accurate evidence is necessary, in addition to investigating the students` perceptions, we should do observational studies of the teaching practices themselves.